Sustainability and sacred values - John Cairns Jr. (Ethics in Science and Environmental Politics, 2002)
Successful implementation of the quest for sustainable use of the planet requires that human society both reexamine and expand present views of what is sacred and what is not. The most important aspect will be going beyond a homocentric focus to a biocentric emphasis. A unifying theme would be the desire to leave a habitable planet for human descendants and those of other species. It is unlikely that society can be confident of achieving sustainability until persuasive evidence supporting this belief has existed for several generations. In order for sustainable use of the planet to persist indefinitely, the conditions essential to this state must be morally preserved on sacred grounds. Viewing natural systems as sacred requires not only preventing damage to them but, wherever possible, repairing damage to them caused by humankind.